2014
DOI: 10.2147/nan.s55721
|View full text |Cite
|
Sign up to set email alerts
|

Androgen responsiveness to competition in humans: the role of cognitive variables

Abstract: Although androgens are commonly seen as male sex hormones, it has been established over the years that in both sexes, androgens also respond to social challenges. To explain the socially driven changes in androgens, two theoretical models have been proposed: the biosocial model and the challenge hypothesis. These models are typically seen as partly overlapping; however, they generate different predictions that are clarified here. In humans, sports competition and nonmetabolic competitive tasks have been used i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
20
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 37 publications
(23 citation statements)
references
References 159 publications
(169 reference statements)
3
20
0
Order By: Relevance
“…All of these effects presumably increase the odds of successful aggression in contexts where status is threatened (reviewed in Eisenegger et al 2011, Montoya et al 2012, Oliveira & Oliveira 2014, Terburg & van Honk 2013). …”
Section: What Is Testosterone Doing?mentioning
confidence: 99%
See 1 more Smart Citation
“…All of these effects presumably increase the odds of successful aggression in contexts where status is threatened (reviewed in Eisenegger et al 2011, Montoya et al 2012, Oliveira & Oliveira 2014, Terburg & van Honk 2013). …”
Section: What Is Testosterone Doing?mentioning
confidence: 99%
“…In multiple competitive contexts it is common for winners to show increases in testosterone, losers to show decreases, or both (reviewed in Archer 2006, Carré & Olmstead 2015, Oliveira & Oliveira 2014). Not all studies find these effects; important moderating factors include whether outcomes are (1) decisive, (2) attributed to individual effort (rather than chance or the effort of others), and (3) interpreted as salient to an individual's status (Carré 2009, Edwards et al 2006, Gonzalez-Bono et al 2000, Mehta et al 2015, Casto & Edwards 2016).…”
Section: What Is Testosterone Doing?mentioning
confidence: 99%
“…Activation of the SAM system affects, amongst others, cardiovascular activity, leading to increased blood pressure and heart rate. Furthermore, testosterone changes have been reported in relation to competitions (for a recent review, see Oliveira and Oliveira 2014) and some studies also found increased testosterone levels after psychosocial stress induction (Lennartsson et al 2012;Bedgood et al 2014). To keep unrelated external influences on the hormonal and physiological measures minimal, a laboratory paradigm was chosen.…”
Section: Aims Of the Present Studymentioning
confidence: 99%
“…The challenge hypothesis more broadly assumes that competitive encounters per se as well as their anticipation elicit an increase in testosterone (Archer 2006). While a range of studies investigated changes in testosterone in response to competitions and competition outcomes (reviewed in Oliveira and Oliveira 2014), only few studies investigated directly whether or not such changes in testosterone influence subsequent competitive behaviours. These studies…”
Section: Reaction To the Game And Choice Of Competitionmentioning
confidence: 99%
“…Testosterone is first and foremost a social hormone, as noted above (and we are an obligatory social species) . How individuals read and react to each other in general—ie, their tendency toward empathy, egotism, competition, cooperation, dominance, fair play, team play, etc—are known to be influenced by testosterone; thus, these social abilities and interactions typically exhibit measurable sexual differences . All of these aspects of neuroprocessing and behavior fall under the broad area of social cognition .…”
Section: Introductionmentioning
confidence: 96%